Mechanical Degradation of Q345 Weathering Steel and Q345 Carbon Steel under Acid Corrosion - Fan Yang; Miao M. Yuan; Wen J. Qiao; Na N. Li; Bin Du (Advances in Materials Science and Engineering)
In this work, a mechanical degradation of weathering steel and carbon steel caused by strong acid corrosion has been studied in order to clarify the threat of industrial acid vehicle leakage to steel structure bridge. Twenty-seven specimens of Q345 weathering steel plates and Q345 carbon steel plates were immersed in a 36% hydrochloric acid solution at room temperature, with the corrosion time being 0 h, 1 h, 2 h, 4 h, 8 h, 12 h, 24 h, 48 h, and 72 h, respectively. Subsequently, the obtained specimens were subjected to a uniaxial tensile test to determine the stress-strain curves. The surface morphology was studied by the noncontact surface topography instrument DSX500. By analyzing the degree of mechanical degradation, the constitutive models of test steels under strong acid corrosion were established. The analysis of results shows that the corrosion rate of carbon steel is higher than that of weathering steel. After 72 hours of corrosion, the mass loss rate of carbon steel and weathering steel was 4.77% and 4.30%, respectively. The maximum corrosion pit depth of carbon steel was 25.52 μm higher than that of weathering steel. The constitutive models were in good agreement with the test results, and the resistance to corrosion degradation and deformation of the weathering steel was higher compared to the carbon steel. The results can serve as a guideline for designing steel constructions of improved durability.